2015
DOI: 10.1108/jfm-11-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of facility management practices in public and private buildings in Akure and Ibadan cities, south-western Nigeria

Abstract: Purpose – This paper aims to assess the facility management (FM) practices in public and private buildings, and compare the practices in both the buildings. This paper critically analysed the current FM practices and explored the range of contributions that the facility manager could offer in both public and private buildings. Design/methodology/approach – A case study of 19 public and 20 private buildings in Ibadan and Akure cities was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 14 publications
4
33
0
1
Order By: Relevance
“…Adenuga (2011) asserted that majority of the Nigerian public hospital buildings are in appalling conditions. This is probably one of the reasons Ogungbile and Oke (2015) suggested stricter action to be taken to reduce poor handling and misuse of public and private buildings by users in Nigeria. Jandali and Sweis (2018) opined that keeping the functional state of the hospital facilities and buildings in good conditions cannot be overemphasised because of possible damage from minor or major maintenance issues if the hospitals are closed.…”
Section: Introductionmentioning
confidence: 99%
“…Adenuga (2011) asserted that majority of the Nigerian public hospital buildings are in appalling conditions. This is probably one of the reasons Ogungbile and Oke (2015) suggested stricter action to be taken to reduce poor handling and misuse of public and private buildings by users in Nigeria. Jandali and Sweis (2018) opined that keeping the functional state of the hospital facilities and buildings in good conditions cannot be overemphasised because of possible damage from minor or major maintenance issues if the hospitals are closed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on public maintenance practices in Ghana and elsewhere have revealed that preventive maintenance, corrective maintenance and condition-based maintenance are most commonly practiced (Lateef, 2010; Ogungbile and Oke, 2015; Yinghua et al , 2018; Nkrumah et al , 2017; De Morais and Júnior, 2019; Alawayasheh et al , 2020). In the case of Ghana, the poor quality of maintenance practices is due to several factors including the lack of good quality management policies which have long-term effects on the management of public infrastructure (Nkrumah et al , 2017).…”
Section: Literature On Maintenance Practicesmentioning
confidence: 99%
“…Notwithstanding the critical role of public property in socioeconomic development, Nkrumah et al (2017) posit that public property maintenance has not been given the desired attention. Hence, sustainable development in most developing countries, particularly in Africa, has been hindered by a gap in the infrastructural requirements and apparent poor maintenance practices in existing public property (Efobi and Anierobi, 2014; Ogungbile and Oke, 2015; Nkrumah et al , 2017). The African Capacity Building Foundation (ACBF) (2016) reports that the annual infrastructure investment requirement for Africa is about $93 billion, one-third of which is for maintenance and operations.…”
Section: Introductionmentioning
confidence: 99%
“…La efectiva gestión de instalaciones físicas se ve reflejada en su valorización y un servicio de calidad a los usuarios finales, tales como empleados del sector público y privado, inquilinos, etc. (Ogungbile y Oke, 2015).…”
Section: Introductionunclassified